The use of immunohistochemistry improves the diagnosis of small cell lung cancer and its differential diagnosis: an international reproducibility study in a demanding set of cases - Thunnissen, Erik; Warth, Arne (Journal of thoracic oncology, 2017)
Introduction: The current WHO classification of lung cancer states that a diagnosis of SCLC can be reliably made on routine histological and cytological grounds but immunohistochemistry (IHC) may be required, particularly (1) in cases in which histologic features are equivocal and (2) in cases in which the pathologist wants to increase confidence in diagnosis. However, reproducibility studies based on hematoxylin and eosin-stained slides alone for SCLC versus large cell neuroendocrine carcinoma (LCNEC) have shown pairwise κ scores ranging from 0.35 to 0.81. This study examines whether judicious use of IHC improves diagnostic reproducibility for SCLC. Methods: Nineteen lung pathologists studied interactive digital images of 79 tumors, predominantly neuroendocrine lung tumors. Images of resection and biopsy specimens were used to make diagnoses solely on the basis of morphologic features (level 1), morphologic features along with requested IHC staining results (level 2), and all available IHC staining results (level 3). Results: For the 19 pathologists reading all 79 cases, the rate of agreement for level 1 was 64.7%, and it increased to 73.2% and 77.5% in levels 2 and 3, respectively. With IHC, κ scores for four tumor categories (SCLC, LCNEC, carcinoid tumors, and other) increased in resection samples from 0.43 to 0.60 and in biopsy specimens from 0.43 to 0.64. Conclusions: Diagnosis using hematoxylin and eosin staining alone showeds moderate agreement among pathologists in tumors with neuroendocrine morphology, but agreement improved to good in most cases with the judicious use of IHC, especially in the diagnosis of SCLC. An approach for IHC in the differential diagnosis of SCLC is provided.